The Effect of Range Of Motion (ROM) Exercise on the Level of Stroke Patient Mobility - Muriyati; Safruddin; Andi Nurwahyuni Asmur (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
One form of mobilization that can be given is by doing ROM exercises. Muscle strength in stroke patients can be done immediately through ROM exercises after a stroke has passed. The impact of ROM exercises that are not immediately performed in stroke patients as early as possible is the occurrence of muscle cell atrophy, joint stiffness, decreased muscle contraction, pain during movement and as a whole will result in the inability to move or activity. The purpose of this study is to investigate the effect of Range Of Exercise Motion (ROM) Against the Level of Mobility of Stroke Patients in the Seruni and Flamboyant Treatment Room of H. Andi Sulthan Hospital, Daeng Radja Bulukumba. This type of research is quantitative research, this type of research uses pre-experimental research, with one group research design pre and posttest design. The sample of this study were 30 respondents taken by purposive sampling method. Data analysis in this study used a statistical test dependent test (paired-sample t-test). The results of the analysis used a paired sample t-test with a level of confidence (α = 0.05). Based on the results of this test, the p-value is 0.007, thus p <α (0.007 <0.05), then Ha is accepted. This study concludes that there is the effect of Range of Motion (ROM) Exercise on the Mobility Level of Stroke Patients in the Seruni and Flamboyant Treatment Room of H. Andi Sulthan Daeng Radja Bulukumba Hospital. Suggestion: It is expected to be able to add information and input for health workers to improve the quality of health services provided and is expected to also provide benefits to the public in terms of information about the importance of the range of motion (ROM) training on the level of mobility of stroke patients